The Impact of the Work Environment on Prison Staff: The Issue of Consideration, Structure, Job Variety, and Training - Lambert, Eric G. (American journal of criminal justice, 2009)
Correctional staff are instrumental in ensuring the success of any correctional institution; therefore, investigating how the work environment impacts correctional workers is essential. To determine the effects of supervisory consideration, supervisory structure, job variety, and perceptions of training on correctional staff job stress, job satisfaction, and organizational commitment, data from a survey of staff at a Midwestern private correctional facility were examined. The Ordinary Least Squares regression results indicate that each of the work environment factors had a significant impact on one or more of the three outcomes. Specifically, supervisory consideration and perceptions of training decreased job stress. Supervisory consideration, job variety, and perceptions of training had positive effects on job satisfaction. Finally, supervisory consideration, supervisory structure, job variety, and perceptions of training had positive relationships with organizational commitment.